Utilization of Tubers to Increase The Income of the Tarowang Village Community, Jeneponto District - Romansyah SAHABUDDIN; Vivit ROSMAYANTI; Asrifan ASRIFAN; Burhanuddin BURHANUDDIN (PT Keberlanjutan Strategis Indonesia, 2025)
The utilization of tubers as a means to enhance community income in Tarowang Village, Jeneponto Regency. Tubers such as sweet potatoes, cassava, and taro are local commodities with high economic potential if managed properly. Using a community empowerment approach, this study examines the potential for processing tubers into various value-added products, including chips, flour, and ready-to-eat foods. The results indicate that the use of tubers not only increases food diversification but also expands opportunities for household-based micro-enterprises. Through training and mentoring, the community can improve product processing skills, expand market access, and develop local and digital marketing strategies. The increase in community income is reflected in the increased scale of production and the growing demand for processed products in the local market. Furthermore, the use of tubers helps strengthen village food security and reduce dependence on imported food products. This study concludes that the development of tuber-based businesses has significant prospects for improving the economic welfare of the Tarowang Village community. Therefore, synergy is needed between the village government, supporting institutions, and the community to optimize local potential through innovation and business sustainability.